Optimalisasi Pemahaman PTK Guru PAUD melalui Workshop Berbasis Praktik Reflektif: Studi Pra-Eksperimental - Asfi Yanti WE; Hukmi Hukmi; Muhammad Nor; Nova Yohana (MAN 4 Kota Pekanbaru, 2025)
Education is the cornerstone of a nation's development, heavily reliant on the proficiency of its educators. Despite this, many teachers face obstacles in executing their roles as defined by teacher competencies, particularly in conducting classroom action research (CAR), which entails identifying developmental issues in children and formulating suitable interventions. This research aims to bolster teachers' grasp of CAR through workshops that emphasize practice and reflection. The research process involves several stages: introducing relevant material, engaging in reflective practice based on personal experience, participating in group discussions, and creating follow-up learning strategies. This study employed a pre-experimental one-group pretest–posttest design involving 10 early childhood teachers. Data from pretest and posttest were analyzed using descriptive statistics, paired-sample t-test, and N-Gain analysis. The effectiveness of this training is assessed by comparing pretest and posttest results. Findings reveal that reflective practice-based workshops significantly enhance early childhood teachers' understanding of CAR. While the improvement in comprehension is considered moderately effective, these workshops offer a valuable framework for advancing other areas of teacher competency.